USING WORD WALLS MEDIA TO HELP IMPROVE THE VOCABULARY ACHIEVEMENT OF THE SECOND YEAR STUDENTS OF SMP NEGERI 5 TAPUNG HILIR - Resi Novalia; Fadly Azhar; M Syarfi M Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This Classroom Action Reserach (CAR) aimed to to prove whether the use of word walls media can improve vocabulary achievement of the second year students of SMP Negeri 5 Tapung Hilir. This research was conducted in two cycles that consisted of four meeting in each cycle. This research was conducted to overcome the existing problem on the field as well as to described and to explain whether the word walls media could improve the students’ vocabulary achievement. The result of this research average score in pre-test is 66,83 average scores in post-test cycle 1 is 69,16 and average scores in post-test cycle 2 is 76,66. The result of this research indicated that the word walls media could improve the students’ vocabulary achievement. It was also found that; The selection of appropriated word walls media; The application of word walls; The management activities of the class & practiced; and teacher support can increase students motivation in vocabulary achievement.Key Words: Improve, Vocabulary Achievement, Word walls.